Examination of England’s New Medicine Service (NMS) of complex health care interventions in community pharmacy - Latif, Asam; Waring, Justin; Watmough, Deborah; Barber, Nick; Chuter, Anthony; Davies, James; Salema, Nde-Eshimuni; Boyd, Matthew J.; Elliott, Rachel A. (Elsevier, 2015)
Background: Community pharmacies are increasingly commissioned to deliver new, complex health interventions in response to the growing demands on family doctors and secondary health care services. Little is known about how these complex interventions are being accommodated and translated into the community pharmacy setting and whether their aims and objectives are realized in practice. The New Medicine Service (NMS) is a complex medicine management intervention that aims to support patients’ adherence to newly prescribed medicines for a long-term condition. Objective: This study explores the recent implementation of the NMS in community pharmacies across England. It also seeks to understand how the service is becoming manifest in practice and what lessons can be learned for future service implementation. Methods: Structured, organizational ethnographic observations and in situ workplace interviews with pharmacists and support staff were undertaken within 23 English community pharmacies. Additionally, one-toone, semi-structured interviews were carried out with 47 community pharmacists and 11 general practitioners (GPs). Observational and interview data were transcribed and analysed thematically and guided by Damschroder’s consolidated framework for implementation research. Results: The NMS workload had been implemented and absorbed into pharmacists’ daily routines alongside existing responsibilities with no extra resources and little evidence of reduction in other responsibilities. Pharmacists were pragmatic, simplifying, and adapting the NMS to facilitate its delivery and using discretion to circumvent perceived non-essential paperwork. Pharmacist understanding of the NMS was found to impact on what they believed should be achieved from the service. Despite pharmacists holding positive views about the value of the NMS, not all were convinced of its perceived benefits and necessity, with reports that many consultations did not identify any problems with the patients’ medicines. GPs were generally supportive of the initiative but were unaware of the service or potential benefits. Poorly developed existing pharmacist-GP relationships impeded implementation. Conclusions: This study identifies the multifaceted and complex processes involved in implementing a new community pharmacy service in England. Community pharmacy workflow, infrastructure, and public and professional relationships all affect NMS implementation. Greater prior engagement with the pharmacy workforce and GPs, robust piloting and a phased rollout together with ongoing support and updates, are potentials strategies to ensure future implementation of pharmacy services meet their intended aims in practice.